Implementation Principle of Prudence in Using Intellectual Property Rights as Collateral for Bank Credit - Agus Widyantoro; Dita Elvia Kusuma Putri (Faculty of Law, University of Jember, Indonesia, 2025)
Government issued PP Number 24 of 2022, which regulates about riches intellectual as a debt guarantee object for financial institutions, banks or financial institutions non-banks to be able to provide financing to creative economy actors. But , in the practice Still there is problem related emptiness law on riches intellectual used as Banking debt guarantees , namely there is no basis for determining the economic value of an Intellectual Property Right , and if the debtor defaults there are obstacles to the execution of the Intellectual Property Right. Problems the cause uncertainty law and consequences institution finance No accommodate use Property Rights Intellectual as object guarantee . Formulation problem in study This are : 1) Position of Property Rights Intellectual Property as guarantee credit Banking in Indonesia, and 2) Realization principle caution in placement of Property Rights Intellectual Property as guarantee credit Banking . The research method of this article is legal research with a regulatory approach and a conceptual approach. The results of this article are first, HKI can be used as an object of fiduciary guarantee and the general fiduciary provisions apply because HKI is a movable object. The mechanism embodiment principle caution in placement of Property Rights Intellectual Property as guarantee credit banking , can done with analysis of the 5 C principles, namely character , capacity , capital , collateral , and condition of economy